Engineering staphylococcal protein A for high-throughput affinity purification of monoclonal antibodies - Amritkar, Vinod; Adat, Satish; Tejwani, Vijay; Rathore, Anurag; Bhambure, Rahul (Biotechnology Advances, 2020)
Protein A chromatography is one of the most widely used purification steps in the manufacturing of the various classes of recombinant and non-recombinant antibodies. Due to the higher cost, lower binding capacity, and limited life cycle of Protein A ligand, this affinity-based purification step is often one of the most significant contributors to the cost of manufacturing of monoclonal antibody (mAb) products. In the last decade, there has been significant progress in improving the Protein A chromatography throughput by designing new engineered Staphylococcal Protein A (SPA) variants with higher dynamic binding capacity, considerable alkaline tolerance, and mild acidic elution pH. This review aims at summarizing the various protein engineering approaches used for improving the throughput of the Protein A-based affinity purification of various immunoglobulins. With biopharmaceutical producers operating under ever-increasing pressure towards reducing the cost of manufacturing, these advances in engineered protein A variants will help in processing larger cell culture volumes with high throughput and thereby significantly lower the cost of raw materials.
Keywords: Alkaline tolerance; Dynamic binding capacity; Elution pH; Monoclonal antibodies; Protein A